PERBANDINGAN TINGKAT KESEGARAN JASMANI SISWA YANG MENGIKUTI EKSTRAKURIKULER PENCAK SILAT DAN SISWA YANG TIDAK MENGIKUTI EKSTRAKURIKULER PENCAK SILAT DI SMP BAHRUL ULUM SURABAYA - TOIMUL KHAFID, AHMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Sport is something that is closed related to human’s life physically and spiritually. Physical education is a part of education which totally puts the physical activity and heath life pattern in the priority for the physical, mental and emotional growth and development. This research aims to find out if there is a difference of Pyhsical Fitness degree of students who join “Pencak Silat” extracurricular and those who do not. The sample is taken by using random sampling and purposive sampling method. It is a sample collection technique in which the characteristics have been recognized before based on the population features or characteristics. This research is comparative research. It is a research which compares a group of sample with another group of sample based on the certain variables or measurements. The populations in this research are the seventh grade and the eighth grade students of Junior High School Bahrul Ulum Surabaya. Indonesia Test Of Pyhsical Fitnes (TKJI) is used to collect data. Based on the research result, it is known that on average the students who join “Pencak Silat” extracurricular amounts 14.76 with the deviation standard 1,964. On the other hand, the students who do not join “Pencak Silat” amounts 14,32 on average with the deviation standard 2,322 . By doing calculation using Statistical Program for Social Science (SPSS) for windows evaluation 20, the t–test analysis obtained is thitung(0,723) <ttabel(2,0105). In other words, there is no difference. Therefore, Ha is rejected and Ho is accepted. It can be concluded that there is no difference of body fitness degree of students who join “Pencak Silat” extracurricular and those who do not. Keywords : Pyhsical Fitness, extracurricular and non extracurricular, Pencak Silat.